The Implementation of Digital Productive Zakat Management Strategy at Musa'adatul Ummah - Jamaludin, Jujun; Nasution, Ade Iskandar; Jalaluddin, Jalaluddin; Wijana, Miki (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aims to analyze the strategy of productive zakat management in the digital era as implemented by the Zakat Management Institution Musa'adatul Ummah. A qualitative approach using a case study method was employed to gain in-depth understanding of the institution’s strategic efforts in empowering zakat recipients (mustahik). The findings reveal that the strategy focuses on the selection of potential mustahik, the provision of business capital in the form of non-repayable grants, and intensive mentoring in entrepreneurship. The institution has also begun utilizing digital technology to enhance efficiency and effectiveness, particularly in fundraising through digital platforms, program promotion via social media, and zakat distribution reporting in the form of digital infographics. However, the digitization process still faces several challenges, such as limited technological infrastructure, insufficient digital competence among human resources, and low digital literacy among mustahik. These findings highlight the need for institutional capacity building, the development of an integrated digital zakat system, and strategic collaboration with various stakeholders to support sustainable digital transformation in zakat management. This study contributes theoretically to the development of a digital-based zakat management model and practically offers insights for local zakat institutions to navigate the challenges of the digital era.